Sports participation of children and adolescents in Germany: disentangling the influence of parental socioeconomic status - Lea Rittsteiger; Thomas Hinz; Doris Oriwol; Hagen Wäsche; Claudia Santos-Hövener; Alexander Woll (BMC, 2021)
Abstract Background Participation in sports and physical activity (PA) is a critical resource for children's health and social development. This study analyzes how the parental socioeconomic status (SES) of children and adolescents affects their PA in sports clubs (organized sports) and outside of sports clubs (unorganized sports) and tests whether the potential impact of parental SES is mediated by the opportunity structure of their residential area (walkability, infrastructure, etc.) and by family and peer support for PA. Furthermore, PA is analyzed respecting differences by gender and migration background. Methods Using representative data from the MoMo/KiGGS study (2009-2012 and 2014-2017), we take into account about 8000 measurements from about 7000 subjects. We estimate hurdle regression models to analyze the minutes per week spent on sports activities. Results Results show that children with a higher parental SES, children living in areas with many opportunities for PA, and children receiving family and peer support are more physically active than children without these features. Controlled for opportunities and support, status effects are small but visible. The differences regarding parental SES are much more apparent for organized sports than for unorganized sports, indicating the relevance of economic resources. Boys are more active than girls, whereas there is no clear effect of migration background. Conclusions The coefficient of parental SES on organized sports most probably relates to the resources needed to participate in sports clubs, including fees and equipment. Lower membership fees might potentially help to integrate children with low parental SES into sports clubs and thereby make organized sports more accessible to all social classes.